FROM COMPLIANCE TO CULTURE: A LONGITUDINAL STUDY ON THE EFFICACY OF MICROLEARNING IN SUSTAINING ETHICAL WORKPLACE BEHAVIOR - Santia Rahmadani; Dhenny Asmarazisa; Catur Fatchu Ukhriyawati (RADJA PUBLIKA, 2026)
The increasing complexity of organizational environments and heightened regulatory scrutiny have intensified the need for effective approaches to promoting ethical workplace behavior. Traditional compliance training programs, while essential for raising awareness, often fail to sustain long-term behavioral change due to their episodic and standardized nature. This study examines the efficacy of microlearning as a continuous learning approach in fostering sustained ethical behavior over time. Adopting a longitudinal research design, data were collected across multiple time points to assess changes in microlearning engagement, ethical awareness, and behavioral outcomes. The findings indicate that microlearning significantly enhances knowledge retention and reinforces ethical principles through repeated exposure. This continuous reinforcement leads to increased ethical awareness, reduced unethical behavior, and improved accountability among employees. Furthermore, the study highlights the role of microlearning in facilitating the transition from compliance-based systems to value-driven ethical cultures. By supporting habit formation and integrating learning into daily work routines, microlearning contributes to the development of sustained ethical behavior. The study offers both theoretical and practical insights into the role of continuous learning in organizational ethics. It concludes that microlearning is a critical tool for embedding ethical behavior within organizational culture and achieving long-term governance effectiveness.